The Cyclical and Long-Term Behavior of Government Expenditures in Developing Countries - Inchauste, Gabriela (IMF Working Papers; Working Paper, 2004)
We examine the short- and long-term movements of government spending relative to output in 51 countries. We find that in the short term, the main components of government spending increase with output in about half of the sample countries, with some variation across spending categories and countries. Further, we find that there is a long-term relationship between government spending and output (in line with "Wagner's law") for the majority of countries for at least one spending aggregate. In the short term, we find that power dispersion and government size typically dampen the positive response of government spending to output. Output volatility and financial risk, on the other hand, contribute to the procylicality of government spending.